Korelasi Antar Komponen Pertumbuhan Vegetatif dan Generatif dengan Hasil pada Delapan Belas Genotipe Gandum di Dataran Tinggi - Novrika, Donda; Herison, Catur; Fahrurrozi, Fahrurrozi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2016)
Indonesia needs to develop high yielding wheat varieties adapted to tropical highland environment, through benefit selection in order to reduce grain imports. Pretiminary studies are often conducted to support the selection of activities to determine whether there is a closeness connection or relationship between variables with other variables through correlation studies. This study aims to determine the level of closeness between vegetative and generative variables and results in each 18 genotypes of wheat grown in the highlands. This study used a randomized complete block design with 3 replications. The treatments are 18 wheat genotypes : M1, M2, M3, M4, M5, M6, M7, M8, M9, SO 3, SO-8, SO- 9, JARISSA, SELAYAR, NIAS, DEWATA, SO-10, SO-6. Results showed that, plant height and number of seeds per panicle were positively correlated closely with yield of grain weight per clump. Plant height of JARISSA and NIAS, and the number of seeds/panicle of M2, M3, M7, JARISSA and NIAS. So that, variable can be used as selection criteria for potential high wheat genotypes grown at higher altitudes in tropical conditions, when the power of inheritance have predictive value (heritability) high. Therefore, these characters can be used as selection criteria for high yielding wheat genotypes.